Domain Requirements for DNA Unwinding by Mycobacterial UvrD2, an Essential DNA Helicase - Sinha, Krishna Murari (2008)
Mycobacterial UvrD2 is a DNA-dependent ATPase with 3′ to 5′ helicase activity. UvrD2 is an atypical helicase, insofar as its N-terminal ATPase domain resembles the superfamily I helicases UvrD/PcrA, yet it has a C-terminal HRDC domain, which is a feature of RecQ-type superfamily II helicases. The ATPase and HRDC domains are connected by a CxxC-(14)-CxxC tetracysteine module that defines a new clade of UvrD2-like bacterial helicases found only in Actinomycetales. By characterizing truncated versions of Mycobacterium smegmatis UvrD2, we show that whereas the HRDC domain is not required for ATPase or helicase activities in vitro, deletion of the tetracysteine module abolishes duplex unwinding while preserving ATP hydrolysis. Replacing each of the CxxC motifs with a double-alanine variant AxxA had no effect on duplex unwinding, signifying that the domain module, not the cysteines, is crucial for function. The helicase activity of a truncated UvrD2 lacking the tetracysteine and HRDC domains was restored by the DNA-binding protein Ku, a component of the mycobacterial NHEJ system and a cofactor for DNA unwinding by the paralogous mycobacterial helicase UvrD1. Our findings indicate that coupling of ATP hydrolysis to duplex unwinding can be achieved by protein domains acting in cis or trans. Attempts to disrupt the M. smegmatis uvrD2 gene were unsuccessful unless a second copy of uvrD2 was present elsewhere in the chromosome, indicating that UvrD2 is essential for growth of M. smegmatis.